Assessing Workload and Wellbeing Among Male School Athletes During a Two-Season Overlap Period - Simphiwe Nkosi; Andrew Green (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The study's goal was to evaluate and track the physical abilities and seasonal workloads of male multisport athletes who struggle with converging sport seasons. Due to the increased training load, these obstacles may have an effect on their general well-being. The researchers monitored the internal workloads of 15 male students who participated in a variety of sports disciplines. Over the course of a 10-week period, they assessed their general preparation and fitness using self-reported questionnaires. Through the course of the monitoring period, statistical analysis revealed substantial variations in workloads and the ACWR (acute to chronic workload ratio) (p = 0.002). Agility, vertical jump power, yo-yo intermittent recovery (Level 1), and predicted VO2max characteristics all showed significant changes (p 0.002). The participants' relatively high wellbeing and ACWR values, however, show that they did not endure enough stress from the workloads to cause physiological changes that would improve their performance. It's probable that the athletes' workloads were reasonable enough to lower the risk of injury while still enhancing performance.